2018
DOI: 10.1016/j.biotri.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Simulator Wear Test of Five Contemporary Total Shoulder Prostheses With Three Axes of Rotation and Sliding Motion

Abstract: Shoulder joint replacement generally utilizes ultra-high molecular weight polyethylene (UHMWPE) as a bearing surface. Long term survival of such implants is recognized to be limited by wear of the UHMWPE. Commercially available JRI 42mm diameter VAIOS Total shoulders were wear tested in diluted bovine serum for five million cycles in a unique Shoulder Wear Simulator. Five Total shoulders were subject to rotational and translational motion, and loading, to replicate the 'Mug to Mouth' activity of daily living. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Humeral head resurfacing is also more effective and protective than the “ream and run” procedure. In the “ream and run” procedure, the glenoid is made smooth by reaming but no glenoid implant is placed [ 4 , 21 , 26 , 27 , 28 ]. A stemmed humeral implant with a prosthetic humeral head articulates with the prepared glenoid.…”
Section: Discussionmentioning
confidence: 99%
“…Humeral head resurfacing is also more effective and protective than the “ream and run” procedure. In the “ream and run” procedure, the glenoid is made smooth by reaming but no glenoid implant is placed [ 4 , 21 , 26 , 27 , 28 ]. A stemmed humeral implant with a prosthetic humeral head articulates with the prepared glenoid.…”
Section: Discussionmentioning
confidence: 99%
“…The UHMWPE wear rate found in the present study was considerably reduced compared with wear rates reported in other shoulder in vitro studies. 14,25,43,[52][53][54][55] Mueller et al 52 reported significantly reduced wear rates for a ceramic humeral head against conventional UHMWPE glenoid compared with a conventional CoCr humeral head against the same glenoid component in an anatomic shoulder wear test. However, both wear results were in the same range as the wear rate reported by Wirth et al 25 with conventional UHWMPE.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of cycles used in the present study is not considered an important limitation given that the wear rate of UHMWPE is linear after an initial bedding-in phase in which the wear rate is typically higher. 25,43,52,55 Thus, it is possible to determine whether our wear rate result is also valid for additional millions of cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation